Pengaruh Profitabilitas Dan Leverage Terhadap Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Variabel Intervening Pada Perusahaan Manufaktur (Makanan Dan Minuman) - Nursinta; Herawati Khotmi; Rusdi (Akuntabel: Jurnal Ilmiah Akuntansi, 2024)
This research aims to determine and analyze the significant and direct influence of profitability and leverage on company value through dividend policy as an intervening variable in food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange (BEI) 2019-2022. The population in this research are food and beverage sector manufacturing companies on the Indonesia Stock Exchange (BEI). This research uses a documentation method with purposive sampling technique. The sample used was 9 companies out of 114 companies. The data analysis method used is Multiple Linear Regression. The research results show that profitability (X1) and leverage (X2) have a significant and direct effect on company value (Y) but dividend policy is unable to mediate between profitability and leverage on company value through dividend policy (Z) as an intervening variable.